Digital Talent Management through Innovative Human Resource Management - Emma Ferda Damayanti; S Suharnomo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This paper examines the impact of innovative Human Resource Management (HRM) strategies on organizational success in the digital era. Over time, companies have increasingly adopted advanced technologies, including the internet, modern devices, social networks, e-learning, and digital platforms, to enhance employee performance and drive growth. These tools have positioned HRM as a critical factor for ensuring organizational survival and competitiveness in a technologically advanced world. The study highlights the effects of digital applications on HR processes such as recruitment, promotion, performance evaluation, employee satisfaction, and staff retention. It emphasizes the need for further development in HR practices to address challenges and seize opportunities in the digital context. The findings reveal that leveraging technology in HRM improves organizational efficiency, enhances employee satisfaction, and supports the development of an adaptable and innovative workforce essential for thriving in a dynamic digital workplace.